A preliminary investigation on upper limb exoskeleton assistance for simulated agricultural tasks - Harith, Hazreen Haizi; Mohd, Muhammad Fuad; Nai Sowat, Sharence (Elsevier, 2021)
Manual harvesting is still prevalent in the agricultural industry. Accordingly, it is one of the largest contributors toward work-related musculoskeletal disorder. The cutting task in oil palm harvesting uses a long pole and involves repetitive and forceful motion of the upper limbs. Exoskeleton technology is increasingly explored to assist manual tasks performance in manufacturing and heavy industries, mainly for reducing discomfort and injuries, and improving productivity. This paper reports an initial investigation on the feasibility of using an upper limb exoskeleton to assist oil palm harvesting tasks. Previous studies highlighted that exoskeletons for agricultural activities should be adaptable to changing field tasks, tools and equipment. The immediate difference in the activity of three muscles were analyzed for a range of harvesting-simulated tasks. Lower activities were observed for tasks involving overhead work when using the prototype. Nevertheless, users’ feedback highlighted that its design should be optimized for better acceptance.